Design patterns Elemets of reusable object - oriented software - Gamma, Erich; Helm, Richard; Johnson, Ralph; Viissides, John (Boston Addison - Wesley, 1995)
In this book, Erich Gamma, Richard Helm, Ralph Johnson, John Viissides introduce the principles of design patterns and then offer a catalog of such patterns. Thus, this book makrs two important contribution. First, it shows the role that patterns can play in architecting complex systems. Second, it provides a very pragmatic reference to a set of well-engineered patterns that the practicing developer can apply to crafting his or her own specific applications.
Keywords: Công nghệ Thông tin